Unraveling near-field and far-field relationships for 3D SERS substrates – a combined experimental and theoretical analysis. Issue 5 (9th February 2016) - Kurouski, Dmitry; Large, Nicolas; Chiang, Naihao; Greeneltch, Nathan; Carron, Keith T.; Seideman, Tamar; Schatz, George C.; Van Duyne, Richard P.
Abstract : Simplicity and low cost has positioned inkjet 3D substrates as the most commonly used SERS platforms for the detection and the identification of analytes down to the nanogram and femtogram levels. Abstract : Simplicity and low cost has positioned inkjet paper- and fabric-based 3D substrates as two of the most commonly used surface-enhanced Raman spectroscopy (SERS) platforms for the detection and the identification of chemical and biological analytes down to the nanogram and femtogram levels. The relationship between far-field and near-field properties of these 3D SERS platforms remains poorly understood and warrants more detailed characterization. Here, we investigate the extremely weak optical scattering observed from commercial and home-fabricated paper-, as well as fabric-based 3D SERS substrates. Using wavelength scanned surface-enhanced Raman excitation spectroscopy (WS-SERES) and finite-difference time-domain (FDTD) calculations we were able to determine their near-field SERS properties and correlate them with morphological and far-field properties. It was found that nanoparticle dimers, trimers, and higher order nanoparticle clusters primarily determine the near-field properties of these substrates. At the same time, the far-field response of 3D SERS substrates either originates primarily from the monomers or cannot be clearly defined. Using FDTD we demonstrate that LSPR bands of nanoparticle aggregates near perfectly overlap with the maxima of the near-field surface-enhanced Raman scattering responses of the 3D SERS substrates. This behaviour of far-field spectroscopic properties and near-field surface-enhanced Raman scattering has not been previously observed for 2D SERS substrates, known as nanorod arrays. The combination of these analytical approaches provides a full spectroscopic characterization of 3D SERS substrates, while FDTD simulation can be used to design new 3D SERS substrates with tailored spectral characteristics.